ROTI maps of Greenland using kriging - Beeck S. S. (Sciendo, 2021)
GNSS satellite signals are affected by the media when traversing Earth’s atmosphere, and the performance of GNSS based positioning and navigation is correlated with these effects. In the ionosphere, the signals are affected by the number of electrons along the signal path which can be quantified by the total electron content. The focus of this article is scintillation effects caused by electrons in the Arctic ionosphere, and the rate of the total electron content index, the ROTI, is used as a measure of the scintillation.